1976
DOI: 10.1051/jphyscol:1976639
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Oxyhemoglobin Radiolysis and Thermolysis by Mössbauer Spectroscopy

Abstract: Résumé. -L'étude des modifications en fonction de la dose du spectre Môssbauer de globules rouges artériels irradiés aux rayons X montre que l'irradiation de Foxyhémoglobine globulaire entraîne la production d'une forme déoxy ligandfree probablement quickly reacting comme dans le cas, bien connu, de la photodissociation ainsi que d'une hémoglobine ferrique high spin. Pour des doses de radiation croissantes, Thème de ces radioproduits est détruit et un composé final du type ferrique high spin à environnement rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It should be noted that earlier study of oxyhemoglobin in red blood cells exposed to X-rays by Mo ¨ssbauer spectroscopy showed oxyhemoglobin deoxygenation while protein destruction led to formation of two species: a hemochrome-like compound and a non-heme Fe(III) compound that was considered as a final product of protein destruction. 48,49 Mo ¨ssbauer spectra of oxyhemoglobin exposed to microwave heating (2.45 GHz, 900 W) for 5 and 15 s demonstrated an increase of oxyhemoglobin spectral line width and the formation of a ferric compound. 46 Mo ¨ssbauer parameters of oxyhemoglobin subspectra revealed almost the same values of DE Q and d as those for a non-irradiated oxyhemoglobin sample.…”
Section: Environmental Factorsmentioning
confidence: 96%
“…It should be noted that earlier study of oxyhemoglobin in red blood cells exposed to X-rays by Mo ¨ssbauer spectroscopy showed oxyhemoglobin deoxygenation while protein destruction led to formation of two species: a hemochrome-like compound and a non-heme Fe(III) compound that was considered as a final product of protein destruction. 48,49 Mo ¨ssbauer spectra of oxyhemoglobin exposed to microwave heating (2.45 GHz, 900 W) for 5 and 15 s demonstrated an increase of oxyhemoglobin spectral line width and the formation of a ferric compound. 46 Mo ¨ssbauer parameters of oxyhemoglobin subspectra revealed almost the same values of DE Q and d as those for a non-irradiated oxyhemoglobin sample.…”
Section: Environmental Factorsmentioning
confidence: 96%
“…Mössbauer spectroscopy can be used to investigate some molecular mechanisms of biological effects of exogenous agents. The study of deoxy-and oxyhemoglobin irradiated by X-rays identified iron containing compounds resulting from radiolysis of proteins and showed differences of both hemoglobin forms destruction [52,53]. Another study of oxyhemoglobin radiolysis demonstrated the formation of different products of protein damage by γ-rays of various energies, by electrons and by microwave heating [54][55][56][57][58].…”
Section: Study Of the Effect Of Environmental Factorsmentioning
confidence: 99%